DEVELOPING KAMISHIBAI MEDIA IN TEACHING WRITING DESCRIPTIVE TEXT FOR TENTH GRADE STUDENTS AT SMA YPI AMIR HAMZAH MEDAN - Tria Rizky Nadya Ayu; Rahmad Husein (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
The objective of this study were to develop Kamishibai media in writingdescriptive text for the tenth grade students at SMA YPI Amir Hamzah Medan.The subjects of this research were the tenth grade English teacher, and one classof the tenth grade students in SMA YPI Amir Hamzah Medan. This study wasconducted by using educational Research and Development (R & D) method. Thedata were collected through observation, interview, and questionnaire. Based onthe need analysis from questionnaire and interview, it was known that the studentsneeded a learning media that can make their teaching-learning process easier forthem to understand about the descriptive text and also make the students’experience in learning the descriptive text become interactive, especially in theprocess of writing. As result, the researcher developed Kamishibai for teachingwriting of descriptive text for the tenth grade students at SMA YPI Amir HamzahMedan. The score of validation from the validators was 91,4% and it wascategorized as relevant. It means that the media are valid and appropriate to use aslearning media of writing descriptive text for the tenth grade students at SMA YPIAmir Hamzah Medan.